2013
DOI: 10.2478/popore-2013-0014
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular hydrolytic enzyme production by proteolytic bacteria from the Antarctic

Abstract: Cold−adapted marine bacteria producing extracellular hydrolytic enzymes are important for their industrial application and play a key role in degradation of particulate or− ganic matter in their natural environment. In this work, members of a previously−obtained protease−producing bacterial collection isolated from different marine sources from Potter Cove (King George Island, South Shetlands) were taxonomically identified and screened for their ability to produce other economically relevant enzymes. Eighty−ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Moreover, the relative abundance of Pseudoalteromonas and Colwellia increased during the infection period. Previous studies have shown that Pseudoalteromonas and Colwellia seaweed isolates are capable of agar degradation (Sańchez Hinojosa et al, 2018), with some Pseudoalteromonas producing cold-adapted hydrolytic enzymes and exhibiting high agar-hydrolyzing activity, even at low temperatures (Hollants et al, 2013;Tropeano et al, 2013;Ivanova et al, 2014;Borchert et al, 2017;Sánchez Hinojosa et al, 2018). Other Pseudoalteromonas isolates have been identified as causative agents of disease of Laminaria japonica (Sawabe et al, 1998) and S. japonica (Zhang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the relative abundance of Pseudoalteromonas and Colwellia increased during the infection period. Previous studies have shown that Pseudoalteromonas and Colwellia seaweed isolates are capable of agar degradation (Sańchez Hinojosa et al, 2018), with some Pseudoalteromonas producing cold-adapted hydrolytic enzymes and exhibiting high agar-hydrolyzing activity, even at low temperatures (Hollants et al, 2013;Tropeano et al, 2013;Ivanova et al, 2014;Borchert et al, 2017;Sánchez Hinojosa et al, 2018). Other Pseudoalteromonas isolates have been identified as causative agents of disease of Laminaria japonica (Sawabe et al, 1998) and S. japonica (Zhang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, many agarases have been obtained from microorganisms from different environments, including sediment, seawater, and macroalgae. In the past 20 years, multiple studies have focused on macroalgae-associated bacteria and their production of polysaccharide-degrading enzymes (Tropeano et al, 2012(Tropeano et al, , 2013. However, there are few reports about polysaccharidedegrading enzymes obtained from the macroalgae-associated bacteria collected from Antarctica.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, those actinomycetes which produce a wide spectrum of extracellular lytic ezymes are the ones with the greatest possibilities for successful adaptation to survive there. To thrive in these ecosystems, the actinomycetes should be able to uptake several substrates as nutrients (Tropeano et al, 2013) The perusal of data depicted in Table 5 reveal a significant difference (P<0.05) among actinomycetes in their ability to produce lytic enzymes extracellularly. In terms of chitinase -1 activity, the isolates NA6 and CA1 showed maximum (6.81 U ml ) protease activity (28.13 U ml ) was recorded for isolate NA7.…”
Section: Determination Of Lytic Enzymes Production By Actinomycetesmentioning
confidence: 99%